Legal Protection for Victims of Domestic Violence in Indonesia - Nabila Hilmy Khairunnisa Hasibuan; Salwa Khairina Azzahra; Aqtika Deeba Lubis; Ahmad Asri Nasution (ISNU Sumatera Utara, 2025)
Domestic violence (DV) is a form of human rights violation that remains prevalent in Indonesia. Legal protection for victims of domestic violence has been regulated in various laws and regulations, but its implementation still faces a number of obstacles. This article aims to analyze the forms of legal protection provided to victims of domestic violence in Indonesia and examine the extent to which these regulations are effectively implemented. This research uses a qualitative method with a normative juridical approach sourced from secondary data in the form of laws, journals, and relevant literature. The results of this study indicate that despite the existence of an adequate legal framework, challenges in the form of a patriarchal culture, a lack of understanding among law enforcement officials, and limited access to protection services are the main obstacles to providing optimal protection for victims.